Fluorinated maleimide-substituted porphyrins and chlorins: synthesis and characterization - Ol’shevskaya, Valentina A (Beilstein J Org Chem, 2019)
Maleimide-containing fluorinated porphyrins and chlorins were prepared based on the reaction of Zn(II) or Ni(II) complexes of 5,10,15,20-tetrakis(4-amino-2,3,5,6-tetrafluorophenyl)porphyrin and chlorin with maleic anhydride. Porphyrin maleimide derivatives were also prepared by the reaction of 5,10,15,20-tetrakis(4-azido-2,3,5,6-tetrafluorophenyl)porphyrinato Zn(II) or Ni(II) with N-propargylmaleimide via the CuAAC click reaction to afford fluorinated porphyrin–triazole–maleimide conjugates. New maleimide derivatives were isolated in reasonable yields and identified by UV–vis, (1)H NMR, (19)F NMR spectroscopy and mass-spectrometry.